AGE OF MARRIAGE - A SOCIAL PSYCHOLOGICAL FACTOR OF ENSURING FAMILY STABILITY (Scientific journal of the Fergana State University, 2024)
In this article, family and marriage have been recognized as sacred values ​​in our independent Uzbekistan in recent years, so the science of family, more precisely, getting married, building a family, achieving happiness, raising virtuous, patriotic, intelligent and righteous children , the science of bringing to maturity is of interest to many people, and when analyzed from a scientific point of view, the young family is a unique social group that exists in society, and in turn, it is important for the perspective development and ideological state of the state and society. and the stability of a young family, the time it takes for it to independently solve various household problems is actually a sign of the sincere relationship of two married people to each other, harmonious views of the family and its surrounding values, an example in the parental family information about the social and psychological nature of the factors directly related to the age of marriage.